The Influence of Perceived Sacrifices on Behavioral Intentions in The LGBT Tourism Sector - Nkosivile W. Madinga; Marle van Eyk; Felix Amoah (SAGE Open)
This study aims to investigate the perceived sacrifices associated with visiting an LGBT-friendly destination and its impact on customer value. Specifically, we sought to explore the relationship between customer value, tourist loyalty, and willingness to pay among LGBT tourists. Using a self-administered electronic questionnaire, we collected data from 406 LGBT tourists and employed partial least squares structural equation modelling (PLS-SEM) to analyze the data. The findings of this study reveal that perceived sacrifices, both monetary and non-monetary, are significant antecedents of customer value in the context of LGBT tourism. Moreover, our results demonstrate that customer value has a significant positive impact on tourist loyalty and willingness to pay, highlighting the importance of creating a positive customer experience for this niche market. This study contributes to the growing body of literature on LGBT tourism by providing insights into the factors that drive customer value in this sector. Moreover, our findings offer valuable implications for the tourism industry, highlighting the need to prioritize LGBT-friendly policies and initiatives to attract and retain this significant customer segment. This study sheds light on the perceived sacrifices and customer value in LGBT tourism, offering valuable insights for industry stakeholders seeking to better understand and serve this diverse and growing market.